Increasing Interest in English Teaching through “Picture Cards” in Class X IPS MA Al-Djufri Pamekasan - Lukluk Ibana; Ervina Kamalia; Hilawatuttilawah (PT. Penerbit Tiga Mutiara, 2024)
This study aims to increase students’ interest in learning English by using picture card media through Classroom Action Research (PTK) method. The subjects of the study were students of class X IPS MA Al-Djufri Pamekasan who experienced low interest in learning English. This research was conducted in two cycles, where each cycle consisted of planning, implementation, observation, and reflection stages. Data collected through observation and questionnaires were analyzed to determine the development of students’ interest in learning. The results showed that the use of picture cards could significantly increase students’ interest in learning. In cycle I, the level of students’ interest in learning was recorded at 60%, which indicated a lack of active involvement and motivation in learning English. After the implementation of picture cards in cycle II, students’ interest in learning increased to 83%. This increase can be seen from the increased participation of students in teaching and learning activities, enthusiasm in discussions, and better ability to understand the material. The application of picture cards proved to be effective in attracting students’ attention and facilitating the understanding of English materials, especially vocabulary and sentence structure. This study is in line with visual learning theory which states that the use of visual media can improve students’ memory and engagement. Thus, the use of picture cards as learning media is recommended for English teachers to improve students’ interest and learning outcomes. Further research is expected to explore the use of other media in foreign language learning.